Conceptions and Practices of Equity in Research-Practice Partnerships. Issue 1 (January 2023) - Farrell, Caitlin C.; Singleton, Corinne; Stamatis, Kristina; Riedy, Robbin; Arce-Trigatti, Paula; Penuel, William R.
This framework explores the plurality of ways that research-practice partnerships (RPPs) conceptualize issues of equity, and with what consequences for what gets studied, whose voices are included in inquiry, and what knowledge is foregrounded in partnership activity. We draw on institutional theory and the perspectives of members from diverse partnerships to create a framework on the beliefs and practices of equity in RPPs. In terms of their missions, RPPs' conceptions of equity ranged from a focus on individualism and standardization, to advancing goals of identity, culture, and belonging and attending to power, justice, and anti-racism. Equity was reflected within processes for working together, varying across coordination, collaboration, or transformation of roles and power dynamics. For RPPs, the framework can help develop a common language and shared meanings. For future research, it can serve as an analytic lens to understand when and how RPPs work in service of educational transformation and change.